Stability characteristics of Pt1Ni1/C as cathode catalysts in membrane electrode assembly of polymer electrolyte membrane fuel cell - Cho, Yong-Hun; Jeon, Tae-Yeol; Yoo, Sung Jong; Lee, Kug-Seung; Ahn, Minjeh; Kim, Ok-Hee; Cho, Yoon-Hwan; Lim, Ju Wan; Jung, Namgee; Yoon, Won-Sub; Choe, Heeman; Sung, Yung-Eun (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
To understand the difference in degradation characteristics between carbon-supported platinum (Pt/C) and platinum-nickel alloy (Pt1Ni1/C) cathode catalysts in membrane electrode assemblies (MEAs) of a polymer electrolyte membrane fuel cell (PEMFC), constant current operation of MEA in a single cell was conducted for 1100 h. A significant change in cell potential for the Pt1Ni1/C MEA was observed throughout the test. High-resolution transmission electron microscopy showed that sintering and detachment of metal particles in the Pt1Ni1/C catalyst occurred more sparingly than in the Pt/C catalyst. Instead. X-ray photoelectron spectroscopy element mapping revealed dissolution of Ni atoms in the Pt1Ni1 catalysts even when the Pt1Ni1/C catalyst used in the MEA was well synthesized. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: IMPROVED DURABILITY; SUPPORTED PLATINUM; ALLOY CATALYSTS; REDUCTION; NI; ELECTROCATALYSTS; DISSOLUTION; CORROSION